Perspectives on Information - Ramage, Magnus (Magnus Alastair), 1970-; Chapman, David (David Alan), 1958- (New York : Routledge, 2011)
'Information is everywhere, and defines everything in today's society. Moreover, information is a key concept in a wide range of academic disciplines, from quantum physics to public policy. However, these disciplines all interpret the concept in quite different ways. This book looks at information in several different academic disciplines - cybernetics, ICT, communications theory, semiotics, information systems, library science, linguistics, quantum physics and public policy.'Perspectives on Information' brings clarity and coherence to different perspectives through promoting information as a unifying concept across the disciplinary spectrum. Though conceived as a contribution to the ongoing conversation between academic disciplines into the nature of information, the deliberately accessible style of this text (reflecting the authors' backgrounds at The Open University) will be make it valuable for anyone who needs to know something more about information. Given the ubiquity of information in the 21st century, that means everyone'--
Includes bibliographical references and index.
Keywords: Information theory